Analisis Pola Mengajar Guru Berbagai Usia dalam Mengajar Kitab Kuning di MAS Al-Washliyah 01 Medan - Iqlima Saputri Saragih; Rustam Rustam; Dedi Masri (Pusat Riset dan Inovasi Nasional, 2024)
The purpose of this research is to find out (1) what the teaching patterns of baby boomers generation teachers are in teaching the yellow book at MAS Al-Washliyah 01 Medan, (2) what the teaching patterns of generation X teachers are in teaching the yellow book at MAS Al-Washliyah 01 Medan, ( 3) what are the teaching patterns of Millennial generation teachers in teaching the yellow book at MAS Al-Washliyah 01 Medan. The type of this research is qualitative research. Qualitative research is presenting the results in the form of narrative descriptions. This research uses a phenomenological approach which is usually used to reveal the meanings of human behavior. Data collection uses interviews, observation and documentation. The data analysis technique in this research uses the Miles & Huberman interactive data analysis model. There are three streams of activities which simultaneously reduce data, present data, formulate conclusions, and verify data analysis. The results of the research show that (1) the teachers of the baby boomers generation, generation is in the book. (2) Then all the teachers who teach the yellow book have carried out their roles well, namely as educators, managers, administrators, supervisors, leaders, innovators, facilitators and evaluators. (3) However, the teaching patterns of teachers from the baby boomers generation, generation